2005
DOI: 10.1590/s1516-635x2005000400008
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory water consumption of broilers submitted to water restriction from 1 to 21 days of age

Abstract: A hundred and fifty male Ross 308 broilers were submitted to water restriction (WR) in different levels (0 to 40%) until 21 days of age. The birds received water ad libitum from 22 to 28 days of age and the compensatory consumption of water (CConW) was calculated as the difference in water intake between birds submitted and not submitted to WR. All WR groups showed a compensatory consumption of water, mainly during the first days of the ad libitum period. The water intake in such groups decreased as the birds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
2
6
0
Order By: Relevance
“…In the light of the comparative losses as caused by disease and by vaccination, it is suggested that vaccines be cautiously applied. The compensatory growth observed in vaccinated birds in the present study wasalso reported in other studies that used feed restriction (Plavnik & Hurvitz, 1985), water restriction (Viola et al, 2005), and heat stress (Ribeiro et al, 2001). Compensation is supposed to occur due to a decrease in energy requirements for bird maintenance during the stress period, and provides the advantage of changing bird growth pattern.…”
Section: Resultssupporting
confidence: 87%
“…In the light of the comparative losses as caused by disease and by vaccination, it is suggested that vaccines be cautiously applied. The compensatory growth observed in vaccinated birds in the present study wasalso reported in other studies that used feed restriction (Plavnik & Hurvitz, 1985), water restriction (Viola et al, 2005), and heat stress (Ribeiro et al, 2001). Compensation is supposed to occur due to a decrease in energy requirements for bird maintenance during the stress period, and provides the advantage of changing bird growth pattern.…”
Section: Resultssupporting
confidence: 87%
“…The results were in line with [1] who reported that water intake increase as the feed intake increased. Water consumption in treatment 1, 2, and 4 were in agreement with 285.72 ml/b/d recommended by [43] but lower than 574 ml/b/d reported by [44].…”
Section: Water Consumptionsupporting
confidence: 87%
“…This observation was in line with [39] who observed that at 75% replacement level, the smell of fermented locust bean seed mask the smell of other ingredients, making the diet unacceptable and unpalatable to rabbits. [40], reported a similar observation when he fed rumen content to broilers. However, [41] reported that feed intake increases in animals if the aroma of their diet is pleasant.…”
Section: Feed Intakementioning
confidence: 58%
“…Thirst has been defined as a motivation to search for and ingest water (Kyriazakis and Tolkamp, 2011). This definition implies that behavioural measures of thirst are increased water intake (compensatory water consumption; Viola et al, 2005;Sprenger et al, 2009) and reduced latency to drink after a period of water deprivation. Correspondingly, compensatory feed consumption and reduced latency to eat are used as measures of hunger (e.g.…”
Section: Introductionmentioning
confidence: 99%